Black duck [compact disc, unabridged] - Lisle, Janet Taylor (Random House/Listening Library, 2007)
Years afterwards, Ruben Hart tells the story of how, in 1929 Newport, Rhode Island, his family and his best friend's family were caught up in the violent competition among groups trying to control the local rum-smuggling trade.